Resistance training induces improvements in range of motion: a systematic review and meta-analysis - Alizadeh, S.; Daneshjoo, A.; Zahiri, A.; Anvar, S. H.; Goudini, R.; Hicks, J. P.; Konrad, A.; Behm, D. G. (Sports Medicine, 2023)
Background: Although it is known that resistance training can be as effective as stretch training to increase joint range of motion, to date no comprehensive meta-analysis has investigated the effects of resistance training on range of motion with all its potential affecting variables. Objective: The objective of this systematic review with meta-analysis was to evaluate the effect of chronic resistance training on range of motion compared either to a control condition or stretch training or to a combination of resistance training and stretch training to stretch training, while assessing moderating variables. Design: For the main analysis, a random-effect meta-analysis was used and for the subgroup analysis a mixed-effect model was implemented. Whilst subgroup analyses included sex and participants` activity levels, meta-regression included age, frequency, and duration of resistance training. Data Sources: Following the systematic search in four databases (PubMed, Scopus, SPORTDiscus, and Web of Science) and reference lists, 55 studies were found to be eligible. Eligibility Criteria: Controlled or randomized controlled trials that separately compared the training effects of resistance training exercises with either a control group, stretching group, or combined stretch and resistance training group on range of motion in healthy participants. Results: Resistance training increased range of motion (effect size [ES] = 0.73; p < 0.001) with the exception of no significant range of motion improvement with resistance training using only body mass. There were no significant differences between resistance training versus stretch training (ES = 0.08; p = 0.79) or between resistance training and stretch training versus stretch training alone (ES = - 0.001; p = 0.99). Although "trained or active people" increased range of motion (ES = 0.43; p < 0.001) "untrained and sedentary" individuals had significantly (p = 0.005) higher magnitude range of motion changes (ES = 1.042; p < 0.001). There were no detected differences between sex and contraction type. Meta-regression showed no effect of age, training duration, or frequency. Conclusions: As resistance training with external loads can improve range of motion, stretching prior to or after resistance training may not be necessary to enhance flexibility.